Evaluation of the effects of 20 nm nano-iron oxide particles on fetal heart development in vivo and in vitro on NMRI mice: Nano-iron Oxide Particles and Heart Development - Mirzaei, Sepideh; kaveh Bakhshayesh, Maryam; Parivar, Kazem; Hayati Roodbari, Nasim; Badiei, Alireza (Archives of Advances in Biosciences, 2021)
Introduction: Researchers take a great interest in nanoparticles due to their unique properties and high level of performance. Yet, despite the functions of nanoparticles in various sciences and industries, their potential effects on human health especially fetal heart have not been fully investigated. The destructive effect of iron nanoparticles on the fetal heart is inevitable. Therefore, the aim of this study was to investigate the effect of iron oxide nanoparticles on fetal heart growth and development in vivo and in vitro on NMRI mice. Materials and Methods In this study, mice were divided into three groups: 1- Control: (without the effect of iron oxide), 2- Sham: (injection of solvent iron oxide and distilled water on the 9th day of pregnancy) 3- Treatment: (under the influence of different concentration of nano-iron oxide particles (10, 30, and 50 µg/kg body weight) on the 9th day of pregnancy). On day 16 of pregnancy, fetuses were taken out and their heart was removed (in vivo method) and analyzed by morphological, histological, and statistical criteria. As for in vitro method, pregnant mice were anesthetized on day 15. The embryos were removed from the body. Their hearts were separated and cultured in a culture medium containing a certain dose of iron oxide nanoparticles. Then, morphological and histological changes were examined. Results: Injection of iron nanoparticles at concentrations of 10, 30, and 50 g/kg caused a significant increase in fetal body weight and height. However, in the results of the examinations on the heart organs, no change in the diameter, weight, wall thickness of the ventricles and atria was observed both macroscopically and microscopically. Conclusions: In the findings of our study, increase in body length and weight of fetuses can significantly indicate the possibility of increased cell division in the fetus and the ability of these nanoparticles to pass through the placenta and transfer from mother to fetus.